(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Background: Motherhood, an eternal, universal and inherent dream which every woman has. This dream may not always be pleasant and it can involve nightmares. One of this is ectopic pregnancy: A pregnancy which can be life threatening. Aims : 1. To know the age group, parity, gestational age and the risk factors with re-spect to the ectopic pregnancy. 2. To know the clinical presentation of the ectopic pregnancy. 3. To know the treatment and morbidity and mortality associated with ectopic pregnancy. Materials & methods : A total of 47 admitted patients who were di-agnosed as ectopic pregnancy cases were retrospective analyzed between the periods from January 2013 to June 2014 at Chattagram Maa-O-Shishu Hospital Medical College, Agrabad, Chittagong. The following parameters: age, parity, gestational age, risk factors, clinical presentation, need for blood transfusion and findings on ultrasonogram and at surgery and morbidity associated with ectopic pregnancy were noted. Results: The incidence of the ectopic pregnancy in the pres-ent study was 7.4/1000 deliveries. A majority of the cases were multigravidas and majority of the cases gestational age were six to ten weeks. In most of the cases, there were no identifiable risk factors. The commonest risk factors present were history of MR (12.7 %)and abortion (10.6), history of tubal surgery (2.2%), infertility (2.2%) and pelvic inflammatory diseases (4.2%).The commonest symptoms were abdominal pain (89.3%), amenorrhea (78.7%) and abnormal vaginal bleeding (63.5%); and commonest signs were abdominal tenderness (70.5%), cervical excitation (52.6%) and adnexal tenderness (50.4%). Almost half (45%) were in a state of shock at admission. Ultrasound, a urine pregnancy test and serum B-hCG were the investigative modalities which were used. Surgery by open method in the form of salpingectomy (92.3%), salpingo-oophorectomy (5.5%) and salpingostomy (2.1%) were the mainstay of management. Morbidity included anemia (50.9%), blood transfusion (78%) and wound infection (2.1%). No maternal mortality noted. Conclusion: Early diagnosis, identifying of underlying risk factors and timely intervention in the form of conservative or surgical treatment will help in reducing the morbidity and mortality associated with ectopic pregnancy. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i3.20993